Translation from Theory to Practice - Nagat A. Radwan; Ayman M. El-Esery (Translation from Theory to Practice, 2022)
The present book is dedicated to translation learners, teachers and trainees. The book tackles translation as a process. It proposes a practical guide for translating using a four steps model, SBTM, for translation process. It offers guidelines upon which translation practicing programs may be constructed to develop translation skills. The book handles the main criteria of acceptable translation, teaching translation, problems of translation, translation strategies, evaluating translation and translation process. As the first step in translating process is comprehension, the book focuses on schema activation before translating. It determines the basic guidelines in translation process considering the cultural, structural and linguistic differences between English and Arabic languages. It highlights the importance of achieving coherence and cohesion of the target text.